Once Upon a Christmas Cheery, in the Lab of Shakhashiri... - Shakhashiri, Bassam Z. (1989)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1989 lecture was the 20th anniversary of the series (not all of which were recorded or televised). This year's lecture includes the combustibility of different elements and chemicals, experiments with solid state carbon dioxide, multiple uses for liquid nitrogen, acid and bases, polymers, and appearances by Bucky, the UW mascot, Santa Claus, and UW chemistry professor Fred Juergens. This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself.
Keywords: Science--Study and teaching; Lectures; Chemistry--Experiments; University of Wisconsin--Madison; Christmas; Liquid nitrogen; Combustion; Chemiluminescence; Santa Claus (Fictitious character)